Pemanfaatan Limbah Enceng Gondok Sebagai Kerajinan Tas - Purnomo, Agus; Hani, Umi; Purnamasari, S; Zahra Maulida, Atika; Hadi, Abdul (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2024)
Water hyacinth is a plant that grows in swamps and rivers. The presence of water hyacinth waste scattered across swamps and rivers makes rivers polluted. Having abundant and rotten water hyacinth waste can have an impact on health. There are empowerment activities for the community to utilize water hyacinth waste into handicrafts in the form of bags. The aim of community service is to utilize water hyacinth waste into craft materials that have sales value. The implementation of this service activity uses socialization methods and training on how to use water hyacinth waste to make handicrafts. Water hyacinth waste is cut into long shapes and then dried in the sun until dry. Results and discussion Water hyacinth waste leaves are taken and formed into the desired pattern. In forming the bag shape pattern, the size and shape of the leaves from the dried water hyacinth leaves will be arranged into handicrafts in the form of bags and other handicrafts.